Secondary Metabolites Help Biocontrol Strain Pseudomonas fluorescens CHA0 To Escape Protozoan Grazing - Jousset, Alexandre; Lara, Enrique; Wall, Luis G.; Valverde, Claudio (My University, 2006)
In soil ecosystems, bacteria must cope with predation activity, which is attributed mainly to protists. The development of antipredation strategies may help bacteria maintain higher populations and persist longer in the soil. We analyzed the interaction between the root-colonizing and biocontrol strain Pseudomonas fluorescens CHA0 and three different protist isolates (an amoeba, a flagellate, and a ciliate). CHA0 produces a set of antibiotics, HCN, and an exoprotease. We observed that protists cannot grow on CHA0 but can multiply on isogenic regulatory mutants that do not produce the extracellular metabolites. The in vitro responses to CHA0 cells and its exoproducts included growth inhibition, encystation, paralysis, and cell lysis. By analyzing the responses of protists to bacterial supernatants obtained from different isogenic mutants whose production of one or more exometabolites was affected and also to culture extracts with antibiotic enrichment, we observed different contributions of the phenolic antifungal compound 2,4-diacetylphloroglucinol (DAPG) and the extracellular protease AprA to CHA0 toxicity for protists and to the encystation-reactivation cycle. The grazing pressure artificially produced by a mixture of the three protists in a microcosm system resulted in reduced colonization of cucumber roots by a regulatory isogenic CHA0 mutant unable to produce toxins. These results suggest that exometabolite production in biocontrol strain CHA0 may contribute to avoidance of protist grazing and help sustain higher populations in the rhizosphere, which may be a desirable and advantageous trait for competition with other bacteria for available resources.